On some Palaearctic click beetles deposited in the Hungarian Natural History Museum, 2 (Coleoptera: Elateridae)* - Németh, T.; Platia, G. (Zootaxa, 2014)
One new genus (Roznerathous gen. n.) and 31 new species of Elateridae are described: Athous szalokii sp. n. (Georgia), Agriotes balikesirensis sp. n. (Turkey), Agriotes rozneri sp. n. (Syria), Agriotes sakaryaensis sp. n. (Turkey), Cardiophorus anatolicus sp. n. (Turkey), Cardiophorus aranyos sp. n. (Afghanistan), Cardiophorus burkus sp. n. (Afghanistan), Cardiophorus dicronychoides sp. n. (Afghanistan), Cardiophorus podlussanyi sp. n. (Turkey), Cardiophorus tenuis sp. n. (Armenia), Coptostethus attilai sp. n. (Spain: Canary Isl.), Coptostethus buci sp. n. (Spain: Canary Isl.), Coptostethus kundratai sp. n. (Spain: Canary Isl.), Craspedostethus ferrugineus sp. n. (Iran), Craspedostethus hirticollis sp. n. (Afghanistan), Dicronychus decoroides sp.n. (Iran), Dicronychus diluvii sp. n. (Turkey), Dicronychus fabiani sp. n. (Iran), Dicronychus gurjevae sp. n. (Afghanistan), Dicronychus ilniczkyi sp. n. (Oman), Dicronychus kandaharensis sp. n. (Afghanistan), Dicronychus karolyvigi sp. n. (Iran), Dicronychus podlussanyi sp. n. (Turkey), Dicronychus povolnyi sp. n. (Afghanistan), Dicronychus quadrimaculatus sp. n. (Afghanistan), Glyphonyx occidentalis sp. n. (Afghanistan), Hartenius marocanus sp. n. (Morocco), Hemicrepidius rahmei (Iran) sp. n., Idotarmonides gracilis sp. n. (Turkey), Roznerathous hellenicus sp. n. (Greece), Oedostethus pektusanicus sp. n. (North Korea). Dicronychus marginalis comb. n. and Dicronychus oxypterus comb. n. New distributional data for species of the genera Aeoloides, Agriotes, Ampedus, Cardiohypnus, Cardiophorus, Cidnopus, Craspedostethus, Dicronychus, Drasterius, Haterumelater, Heteroderes, Hypnoidus, Isidus, Limonius, Liotrichus, Melanotus, Pseudocrepidophorus and Zorochros are given. The females of Astanchus ussuriensis (Gurjeva, 1975); Cidnopus macedonicus Cate et Platia, 1989; Peripontius orchymonti Platia, 2008 and the male of Agriotes barkulensis Jagemann, 1942 were unknown at the time of their description, are figured. With 137 figures.